2008
DOI: 10.1016/j.jpsychires.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Circadian affective, cardiopulmonary, and cortisol variability in depressed and nondepressed individuals at risk for cardiovascular disease

Abstract: Depression is a risk factor for cardiovascular disease (CVD) perhaps mediated by hypothalamicpituitary-adrenal (HPA) axis or vagal dysregulation. We investigated circadian mood variation and HPA-axis and autonomic function in older (≥55 years) depressed and nondepressed volunteers at risk for CVD by assessing diurnal positive and negative affect (PA, NA), cortisol, and cardiopulmonary variables in 46 moderately depressed and 19 nondepressed volunteers with elevated CVD risk. Participants sat quietly for 5-min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Interestingly, this association was not noted in patients without coronary heart disease [16]. Contrary to this, Conrad et al [17] did not note any significant differences in salivary cortisol diurnal variation among 46 depressed subjects at risk for cardiovascular disease compared to 19 subjects without depression.…”
Section: Diurnal Cortisol From Awakening To Bedtimementioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, this association was not noted in patients without coronary heart disease [16]. Contrary to this, Conrad et al [17] did not note any significant differences in salivary cortisol diurnal variation among 46 depressed subjects at risk for cardiovascular disease compared to 19 subjects without depression.…”
Section: Diurnal Cortisol From Awakening To Bedtimementioning
confidence: 83%
“…Cortisol awakening response Huber et al [12] ↓ Awakening cortisol rise in depressed compared with nondepressed Kuehner et al [11] ↓ CAR in those with increased vulnerability to depression Diurnal cortisol profile Van den Bergh et al [14,15] Flatter diurnal cortisol profile with depressive symptoms and increased emotional distress Bhattacharyya et al [16] Flatter diurnal cortisol profile in more depressed Conrad et al [17] No association between depression and diurnal cortisol profile…”
Section: Hpa Axis Hyperactivity Catecholaminesmentioning
confidence: 99%
“…When depressive participants were alone they evidenced lower HRV and higher negative affect, but not when they were engaged in social interactions with a partner, family members, or friends. Conrad et al (2008) found no differences in HRV (measured as RSA adjusted for respiration, LF, VLF during the day between depressed and non-depressed older individuals at risk for CVD (social context was not examined.) An individual's fitness is an important possible mediator of the relationship between depression and HRV.…”
Section: Hrv In Depressed Patients Without Cvdmentioning
confidence: 87%
“…Horan, Green, Kring, and Nuechterlein (2006) found that schizophrenics who reported trait anhedonia on questionnaires did not differ from controls on in vivo hedonic responses to film clips and pleasurable food items. Likewise, Conrad, Wilhelm, Roth, Spiegel, and Taylor (2008) found that although depressed and nondepressed at risk for heart disease have been shown to differ on a laboratory Stressor task (Taylor et al, 2006), these findings were not replicated in daily life, even after controlling for respiration and physical activity. To better isolate both the nature and the source of the divergence, as well as its meaning, clearly it will be useful for studies to acquire laboratory and real-life data from the same individuals and/or to embed controlled stimuli into ESM designs to "calibrate" emotion reactivity (for a longer discussion, see Bylsma & Rottenberg, 2011).…”
Section: Discussionmentioning
confidence: 99%